Buprenorphine Transdermal System Improves Sleep Quality and Reduces Sleep Disturbance in Patients with Moderate‐to‐Severe Chronic Low Back Pain: Results from Two Randomized Controlled Trials. Issue 3 (20th January 2015) - Yarlas, Aaron; Miller, Kate; Wen, Warren; Lynch, Shau Yu; Ripa, Steven R.; Pergolizzi, Joseph V.; Raffa, Robert B.
Abstract: Objective: To evaluate the impact of buprenorphine (Butrans ® ) transdermal System (BTDS) treatment on sleep outcomes for patients with moderate‐to‐severe chronic low back pain (CLBP). Methods: Two enriched‐enrollment, randomized‐withdrawal, double‐blind, controlled trials examined BTDS treatment for patients with moderate‐to‐severe CLBP. Trial I evaluated BTDS 10 and 20 mcg/hour against a placebo control among opioid‐naïve patients. Trial II compared BTDS 20 mcg/hour against a lower‐dose control (BTDS 5 mcg/hour) among opioid‐experienced patients. The patient‐reported Medical Outcomes Study Sleep Scale (MOS‐SS) assessed overall sleep quality (Sleep Problems Index [SPI]), Disturbance, and other sleep outcomes. In each trial, MOS‐SS scores were compared between target treatment and control arms during the 12‐week double‐blind phase. Correspondence of changes in sleep outcomes and pain severity and the degree to which pain reduction mediates treatment impact on sleep outcomes were examined. Results: Medical Outcomes Study Sleep Scale scores were collected from 541 (Trial I) and 441 (Trial II) patients prior to randomization and from 369 (Trial I) and 274 (Trial II) patients at week 12. Patients receiving target treatment showed statistically significantly more improvement in SPI and Disturbance scores at 12 weeks than their respective controls ( P s < 0.05). Improvements in SPI and Disturbance for target treatment arms were statistically larger those of the controls by week 4 of the double‐blind phase. The clinical significance of these differences was not determined. Pain reduction predicted improvements in sleep outcomes. Conclusion: Buprenorphine Transdermal System improved sleep quality and disturbance for opioid‐naïve and opioid‐experienced patients with moderate‐to‐severe CLBP. Benefits of BTDS for these sleep outcomes emerged within 4 weeks and were maintained over the entire 12‐week treatment period.